2021
DOI: 10.1177/13591045211058337
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Admissions to a Refugee Child Mental Health Unit in the Context of the COVID-19 Pandemic

Abstract: Background To examine the admissions to a refugee child outpatient mental health unit in the COVID-19 pandemic and to compare them with the pre-pandemic period. Methods This retrospective observational study, planned through the hospital information system and patient files, included the 1-year number of outpatient unit admissions, sociodemographic, and clinical data. Results Before the COVID-19 pandemic (March 2019–February 2020), a total of 2322 patients (local and refugee) applied to the same unit, and 236 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…In another study, a 50% decrease was reported in admissions to the pediatric psychiatrics outpatient clinic during the pandemic process. 17 , 18 In line with the literature, in our study, the number of admissions to our DPU decreased at a ratio of one-third during the pandemic period.…”
Section: Discussionsupporting
confidence: 89%
“…In another study, a 50% decrease was reported in admissions to the pediatric psychiatrics outpatient clinic during the pandemic process. 17 , 18 In line with the literature, in our study, the number of admissions to our DPU decreased at a ratio of one-third during the pandemic period.…”
Section: Discussionsupporting
confidence: 89%
“…Four studies described increased difficulties in accessing care during the pandemic period [ 28 , 32 , 34 , 35 ]. Closures and reduced care affecting TB and HIV care, vaccination campaigns, outpatient and inpatient child health services, psychiatric services, and entire health centres were described in the studies, including interrupted essential medicine supplies [ 28 , 32 , 34 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Examples were given of decentralising services and prioritising self-care, such as mothers performing mid-upper arm circumference measures to identify malnutrition [ 34 ]. Two studies described remote prescribing, longer prescriptions, and medication delivery [ 32 , 35 ]. Technological adaptations, including telemedicine and WhatsApp communications, were used in some instances to maintain services and overcome information barriers [ 34 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, most studies examined the current mental state of children and adolescents and it was seen that the data in Turkey were mostly related to certain patient groups or settings (emergency admissions, inpatient care) ( Kose et al, 2021 ; Ozbaran et al, 2020 ; Ünver and Perdahlı Fiş, 2021 ). There were studies from Europe evaluating the functioning of the child and adolescent psychiatry outpatient clinics (CAPOC) during the COVID-19 pandemic; however, there were limited studies were showing the functioning of CAPOCs during the COVID-19 pandemic compared with the previous year specifically in Turkey.…”
Section: Introductionmentioning
confidence: 99%